THE INFLUENCE OF HUMAN RESOURCE AUDIT ON EMPLOYEE PERFORMANCE AT PT. SONOKEMBANG WAHANA JAYA - Novi Nur Aini; Fakhruddin Kurnia M (Jurnal Mahasiswa Manajemen, 2025)
This study aims to examine the influence of human resource audits on employee performance using a survey research method. The human resource audit is analyzed through three main variables: audit planning, audit implementation, and audit reporting. Data analysis was conducted using SPSS version 26. The research object is PT Sonokembang Wahana Jaya, with a sample of 67 employees. Primary data were collected through questionnaires distributed to the respondents. The results indicate that audit planning does not have a significant effect on employee performance, with a significance value of 0.352. Audit implementation shows a positive but statistically insignificant effect, with a significance value of 0.014 and a positive regression coefficient. Meanwhile, audit reporting has a positive and significant effect on employee performance, with a significance value of 0.008. These findings suggest that audit reporting is the most influential factor in improving employee performance.